A Coulomb explosion strategy to tailor the nano-architecture of α-MoO3 nanobelts and an insight into its intrinsic mechanism. Issue 17 (24th April 2018) - Zhang, Junli; Zhu, Liu; Yang, Yu; Yong, Huadong; Zhang, Junwei; Peng, Yong; Fu, Jiecai
Abstract : Localized Coulomb explosion occurs in α-MoO3 nanobelts under electron beam irradiation and its origin from positive charging was confirmed. Abstract : Tailoring the nanoarchitecture of materials is significant for the development of nanoscience and nanotechnology. To date, one of the most powerful strategies is convergent electron beam irradiation (EBI). However, only two main functions of knock-on or atomic displacement have been achieved to date. In this study, a Coulomb explosion phenomenon was found to occur in α-MoO3 nanobelts (NBs) under electron beam irradiation, which was controllable and could be used to efficiently create nanostructures such as holes, gaps, and other atomic/nanometer patterns on a single α-MoO3 NB. Theoretical simulations starting from the charging state, charging rate to the threshold time of Coulomb explosion reveal that the Coulomb explosion phenomenon should result from positive charging. The results also show that the multiple charged regions are quickly fragmented, and the monolayered α-MoO3 pieces can then be peeled off once the Coulombic repulsion is sufficient to break the Mo–O bonds in the crystalline structure. It is believed that this efficient and versatile strategy may open up a new avenue to tailor α-MoO3 NBs or other kind of transition metal dichalcogenides via the Coulomb explosion effect.